Visual-Somatosensory Integration and Quantitative Gait Performance in Aging - Mahoney, Jeannette R.; Verghese, Joe (Frontiers in Aging Neuroscience, 2018)
Background: The ability to integrate information across sensory modalities is an integral aspect of mobility. Yet, the association between visual-somatosensory (VS) integration and gait performance has not been well-established in aging. Methods: A total of 333 healthy older adults (mean age 76.53 ± 6.22; 53% female) participated in a visual-somatosensory simple reaction time task and underwent quantitative gait assessment using an instrumented walkway. Magnitude of VS integration was assessed using probability models, and then categorized into four integration classifications (superior, good, poor, or deficient). Associations of VS integration with three independent gait factors (Pace, Rhythm, and Variability derived by factor analysis method) were tested at cross-section using linear regression analyses. Given overlaps in neural circuitry necessary for both multisensory integration and goal-directed locomotion, we hypothesized that VS integration would be significantly associated with pace but not rhythm which is a more automatic process controlled mainly through brainstem and spinal networks. Results: In keeping with our hypothesis, magnitude of VS integration was a strong predictor of pace (β = 0.12, p < 0.05) but not rhythm (β = −0.01, p = 0.83) in fully-adjusted models. While there was a trend for the association of magnitude of VS integration with variability (β = −0.11, p = 0.051), post-hoc testing of individual gait variables that loaded highest on the variability factor revealed that stride length variability (β = −0.13, p = 0.03) and not swing time variability (β = −0.08, p = 0.15) was significantly associated with magnitude of VS integration. Of the cohort, 29% had superior, 26% had good, 29% had poor, and 16% had deficient VS integration effects. Conclusions: Worse VS integration in aging is associated with worse spatial but not temporal aspects of gait performance.